An examination of product development approaches within demand driven chains. Issue 5 (12th November 2018) - Naghi Ganji, Elmira; Shah, Satya; Coutroubis, Alec
Abstract : Purpose: Innovation has been considered as the most important factor in today's global and competitive environments for meeting growth, customer demands and expectations for any product development environment. The purpose of this paper is to examine the concepts of sustainable development, its practices and impacts within demand-driven supply chain (DDSC) environments. This paper is part of a wider project and within later stages of the study, a novel framework will be developed in order to link new product development (NPD) and demand chain management (DCM) aspects from the analysis of the research findings. Design/methodology/approach: This research has adopted the approach of descriptive method which tends to examine demand chain concept and its evolution through recent years, while having a particular focus into NPD projects. Findings: The paper investigates early study models through key findings of the literature that focuses on demand chain and NPD for the use and implementation of sustainability measures within manufacturing environments. The research study highlights the need for incorporation of NPD–DCM through the entire business ecosystem entities and also through the flow of information, materials and resources within the structure of the SC. The study finds out the key hurdles of the companies towards adoption of DDSCs in NPD environments, such as lack of cross-organisational association and lack of innovative demand chain frameworks. Originality/value: The novelty of the research is to develop an early understanding within DDSCs, considering the product development programmes particularly focused on marketing activities. The study provides future researchers with the platform to undertake studies within similar function of DDSC environments.